SURVEY TINGKAT VO2 MAX ANGGOTA TIM EKSTRAKULIKULER FUTSAL PUTRI SMA DI KOTA MOJOKERTO (STUDI PADA ANGOTA TIM EKSTRAKULIKULER FUTSAL PUTRI DI SMA NEGERI 2 MOJOKERTO, SMA NEGERI 3 MOJOKERTO, DAN SMA ISLAM BRAWIJAYA MOJOKERTO) - SUDIBYO, ARIS (Jurnal Prestasi Olahraga, 2013)
Futsal is a ball game played by two teams, each comprised of five members. The goal is to put the ball into the opponent's goal post by moving the ball using the feet. The length of the game is 2x20 minutes with breaking time of 10 minutes and 2x5 minutes of extra time. In Mojokerto, there are some Mojokerto Senior High Schools which have futsal extracurricular, such as SMA Negeri 2 Mojokerto, SMA Negeri 3 Mojokerto, SMA Islam Brawijaya. In futsal coaching course, there are several components that must be considered by the coaches for the team to achieve maximum performances, one component is physical. The dominant charasteristics of the physical conditions in futsal is cardiovasculer endurance. The energy system used are supported by anaerobic and aerobic energy systems. Therefore, to determine durability of futsal players can be measured using by the level of VO2 Max Multistage Fitness Test (MFT). VO2 Max is a measure of capacity of each individual to generate the required energy while endurance activity without experiencing excessive fatigue. The purpose of this study is to determine the level of VO2max female futsal team in SMA Negeri 2, SMA 3 and SMA Islam Brawijaya Mojokerto. This research used non-experimental quantitative research by using quantitative descriptive approach. The results of this study are the average of VO2max of female futsal team member of SMAN 2 Mojokerto of 32.73 ml/kg/min which was included in the medium category, SMAN 3 Mojokerto obtained average of 35.01 ml/kg/min which was included in good category, SMA Islam Brawijaya Mojokerto obtained average of 31.04 ml/kg/min which was included in the medium category. It can be concluded that the average of VO2max of the member of female futsal team SMA 3 Mojokerto is the highest, followed by SMA Negeri 2 Mojokerto, and the last is the member of SMA Islam Brawijaya Mojokerto.   Keywords: futsal, female,VO2max, extracurricular